2012
DOI: 10.5012/bkcs.2012.33.7.2352
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Characteristics of a High-Nitrogen Energetic Material: G(AHDNE)

Abstract: A high-nitrogen energetic salt, 1-amino-1-hydrazino-2,2-dinitroethylene guanidine salt [G(AHDNE)], was synthesized by reacting of 1-amino-1-hydrazino-2,2-dinitroethylene (AHDNE) and guanidine hydrochloride in sodium hydroxide aqueous solution. The theoretical investigation on G(AHDNE) was carried out by B3LYP/ 6-311+G* method. The thermal behaviors of G(AHDNE) were studied with DSC and TG-DTG methods, and the result presents an intense exothermic decomposition process. The enthalpy, apparent activation energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it has been used to design a variety of other nitrogen-rich energetic materials, such as 3,6-di-azido-1,2,4,5-tetrazine . DHT was first synthesized by Hiskey et al in 1990s , and later recognized by several experimental groups, but very few theoretical studies were reported. Hu et al studied the intermolecular interactions of DHT using computational modeling and found that the strong intermolecular hydrogen bonding networks dominantly contributed to the dimers . Consequently, the variations identified on a microscopic level can also affect the macroscopic properties like density, which may further improve the performance of an explosive.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been used to design a variety of other nitrogen-rich energetic materials, such as 3,6-di-azido-1,2,4,5-tetrazine . DHT was first synthesized by Hiskey et al in 1990s , and later recognized by several experimental groups, but very few theoretical studies were reported. Hu et al studied the intermolecular interactions of DHT using computational modeling and found that the strong intermolecular hydrogen bonding networks dominantly contributed to the dimers . Consequently, the variations identified on a microscopic level can also affect the macroscopic properties like density, which may further improve the performance of an explosive.…”
Section: Introductionmentioning
confidence: 99%